Pengembangan E-LKPD Berbasis Kemampuan Berpikir Kritis Pada Materi Makanan Dan Sistem Pencernaan Untuk Peserta Didik Kelas VIII - Yunika, Cantika Putri; Hodijah, Siti Romlah Noer; Biru, Lulu Tunjung; Berlian, Liska (PendIPA Journal of Science Education, 2026)
Current learning requires critical thinking skills, but the problem arises that students do not yet have critical thinking skills. Meanwhile, teachers have not created learning that can develop students' critical thinking skills. This is due to limited time in delivering very dense material. The lack of critical thinking skills can be addressed through learning activities that make students actively involved, namely by using E-LKPD. The purpose of this study was to determine the level of validity and readability of students towards E-LKPD based on critical thinking skills. The research method used was Research and Development (R&D) with the ADDIE development model (analysis, design, development, implementation, evaluation). Data were obtained through observation, interviews, validation, and student readability tests. The results of the study based on experts obtained a percentage of 92.02% with a very valid category and for the readability test obtained a result of 88% with a very good category. From the results of the validation and readability test, it can be concluded that the development of E-LKPD based on critical thinking skills is proven to be very valid and has very good readability.